Security, surveillance and geographical patterns at the 2010 FIFA World Cup in Johannesburg. Issue 3 (9th May 2014) - Fonio, Chiara; Pisapia, Giovanni
<x xml:space="preserve">Abstract</x> This paper analyses the 2010 FIFA World Cup that took place in South Africa by focusing on both security and surveillance dynamics and spatial implications in the city of Johannesburg. While securitisation dynamics and socio‐political legacies have been explored by a substantial body of literature, the activities of the law‐enforcement agencies in a specific urban setting, distinctive geographical patterns and aspects of security governance in South Africa seem to be more fragmented. In this contribution we argue that the tournament represents an important shift in FIFA security governance, namely a shift from reactive patterns of security provisions to more proactive policing approaches. Additionally, we shed light on power dynamics and on trends of securitisation of the urban space, such as the reliance on technology‐based policing which resulted in the implementation of surveillance tools. Symbolic implications and spatial patterns are also discussed with an emphasis on either facility developments or on controversial event‐driven projects. Overall, we contend that despite delivering a safe tournament and reducing crime rates, further investigation is needed to assess surveillance technologies both from a cost‐benefit analysis and from socio‐ethical implications, i.e. the stigmatisation of certain social groups. However, we also argue that inclusionary aspects in relation to event‐driven impositions should be taken into account in the literature on mega‐events in the global South.